216k views
2 votes
2m+7/4(3/4m-5/2)=3/32+1/3m

2 Answers

1 vote

Answer:

m=3/2

Explanation:

User Karambaq
by
5.0k points
7 votes

For this case we have the following equation:


2m + \frac {7} {4} (\frac {3} {4} m- \frac {5} {2}) = \frac {3} {32} + \frac {1} {3} m

We apply distributive property on the left side of the equation:


2m + \frac {21} {16} m- \frac {35} {8} = \frac {3} {32} + \frac {1} {3} m

We add similar terms from the left side:


\frac {53} {16} m- \frac {35} {8} = \frac {3} {32} + \frac {1} {3} m

Add
\frac {35} {8}to both sides:


\frac {53} {16} m = \frac {3} {32} + \frac {1} {3} m + \frac {35} {8}

We subtract
\frac {1} {3} m from both sides:


\frac {53} {16} m- \frac {1} {3} m = \frac {3} {32} + \frac {35} {8}\\\frac {143} {48} m = \frac {1144} {256}\\143m = \frac {1144 * 48} {256}

We simplify:


143m = \frac {54912} {256}\\143m = \frac {13728} {64}\\143m = \frac {3432} {16}\\143m = \frac {858} {4}\\143m = \frac {429} {2}

We divide between 143 on both sides:


m = \frac {429} {2 * 143}\\m = \frac {429} {286}\\m = \frac {33} {22}\\m = \frac {3} {2}

Answer:


m = \frac {3} {2}

User Drxzcl
by
5.8k points